A Sugar‐Based Gelator for Marine Oil‐Spill Recovery. (28th January 2016) - Vibhute, Amol M.; Muvvala, Venkatanarayana; Sureshan, Kana M.
Abstract: Marine oil spills constitute an environmental disaster with severe adverse effects on the economy and ecosystem. Phase‐selective organogelators (PSOGs), molecules that can congeal oil selectively from oil–water mixtures, have been proposed to be useful for oil‐spill recovery. However, a major drawback lies in the mode of application of the PSOG to an oil spill spread over a large area. The proposed method of using carrier solvents is impractical for various reasons. Direct application of the PSOG as a solid, although it would be ideal, is unknown, presumably owing to poor dispersion of the solid through the oil. We have designed five cheap and easy‐to‐make glucose‐derived PSOGs that disperse in the oil phase uniformly when applied as a fine powder. These gelators were shown to selectively congeal many oils, including crude oil, from oil–water mixtures to form stable gels, which is an essential property for efficient oil‐spill recovery. We have demonstrated that these PSOGs can be applied aerially as a solid powder onto a mixture of crude oil and sea water and the congealed oil can then be scooped out. Our innovative mode of application and low cost of the PSOG offers a practical solution to oil‐spill recovery.